Проблемы отрицания в крымскотатарском языке (на примере крымскотатарской литературы) - Селимова, Л.Ш. (Культура народов Причерноморья, 2013)
В любом языке существует такая семантическая категория, как отрицание, образующая
оппозицию утверждению. В настоящее время изучение отрицания приобретает в отечественной
лингвистике всё большее значение. Лингвистическое отрицание относится к сложным языковым
категориям. Оно пронизывает всю лексику и грамматику, имеет различные средства и способы
выражения, сложную семантико-синтаксическую структуру. Как одна из универсальных категорий
языка отрицание также позволяет пролить свет в один из самых интересных векторов
лингвистических направлений - языковую картину мира. В будь-якій мові існує така семантична категорія, як заперечення, твірна опозиції
твердженню. В даний час вивчення заперечення набуває у вітчизняній лінгвістиці всього більшого
значення. Лінгвістичне заперечення відноситься до складних мовних категорій. Воно пронизує всю
лексику і граматику, має різні засоби і способи вираження, складну семантіко-синтаксичну структуру.
Як одна з універсальних категорій мови заперечення також дозволяє пролити світло в один з
найцікавіших векторів лінгвістичних напрямів - мовну картину світу. The article deals with the negation, as a semantic category of the language. The linguistic negation
applies to complex language categories. It permeates the entire vocabulary and grammar, has a variety of
means and modes of expression, complex semantic and syntactic structure. As a universal category of the
language, negation, describes one of the most interesting linguistic area – Humans’ worldview.
The author analyses the category of negation and negation in the Crimean Tatar language as a separate system
in the field of morphology. The theoretical importance of this research is in new methods of analysis in the
Crimean Tatar language.
The results of this work can be used by scientists and academicians to create the comparative grammar of the
Crimean Tatar, Turkish, English and other languages, as well as in teaching practice. The most important part
of this research is the practical base. It comprises works of classic and contemporary writers, scientific articles,
newspapers etc.
The negation as a functional-semantic category consists of two micro fields: negative and positive. Specific
formal language markers are depending on the internal language’s structure.
The category of negation is determined in the Crimean Tatar language as a functional-semantic category with a
strong grammatical core. For the Crimean Tatar language is the predominant morphological way of negation.
The most specialized language units here are affixes.